Join the Dots: assessing a collection of 80 million items at The Natural History Museum, London. (4th May 2022) - Miller, C. Giles; Brewer, Philippa; Carine, Mark; Comerford, Gill; Hardy, Helen; Hart, Andrea; Long, Sarah; Price, Benjamin W.; Smith, Caroline L.; Smith, David A.; Smith, Mel; Stevens, Lil; et al.
ABSTRACT: Collections assessments can inform strategic planning, project management, baseline assessment reports, project cost-benefit analyses, support funding requests and collections advocacy. In 2018, 77 staff at the Natural History Museum, London, took part in a successful collections assessment exercise on its 80 million item collection. 17 questions provided details of the Condition, Importance/Significance, Information available and Outreach use/potential about 2602 Collection Units covering the entire Natural History science departments and Library and Archives. Results can be displayed and filtered via a bespoke dashboard in Microsoft Power BI, accessed via a web link available internally to all staff. The project successfully recorded the expertise of the curatorial staff and produced the first comprehensive assessment of the Natural History Museum's collection. The methodology is outlined here to encourage other institutions to run the same assessment. Future developments in the methodology such as automation of scoring and development of the dashboard are discussed.